2016
DOI: 10.5853/jos.2016.00052
|View full text |Cite
|
Sign up to set email alerts
|

Asian Patients with Stroke plus Atrial Fibrillation and the Dose of Non-Vitamin K Oral Anticoagulants

Abstract: After recent randomized control trials (RCTs), non-vitamin K oral anticoagulants (NAOAs) are now widely being used in patients with atrial fibrillation (AF) worldwide. However, current guidelines for the use of NOACs in patients with AF are derived mostly using a Caucasian population and non-stroke patients. Relatively few Asian patients with AF and stroke are included in the recent RCTs. As a result, the optimal use of NOACs in this particular group of patients is remains to be settled. The optimal dose of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 70 publications
0
38
0
Order By: Relevance
“…Recent real-world practice showed a worldwide trend toward the use of low-dose NOACs. [31][32][33] Because anticoagulation is usually a preventative treatment in AF patients, physicians tend to play it safe by using low-dose NOACs in order to prevent bleeding. Similarly, we observed a high prevalence of low-dose NOAC prescriptions in the present Asian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recent real-world practice showed a worldwide trend toward the use of low-dose NOACs. [31][32][33] Because anticoagulation is usually a preventative treatment in AF patients, physicians tend to play it safe by using low-dose NOACs in order to prevent bleeding. Similarly, we observed a high prevalence of low-dose NOAC prescriptions in the present Asian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…2). 30,54 In addition, there is an increasing percentage of AF patients undergoing PCI, where combination therapy of DOAC and antiplatelet therapy is required.…”
Section: Use Of Oral Anticoagulants In East Asiansmentioning
confidence: 99%
“…Compared to non-Asians, Asians are at significantly higher risk of warfarin-related intracranial bleeding (HR = 4.06) [2]. Although NOAC trial meta-analysis demonstrated greater proportional reduction compared with warfarin for rates of intracranial haemorrhage for Asian patients versus non-Asians, the absolute rates still remain higher [4,11]. Attention has also been focused on the possible link between macro and micro-angiopathies which are more prevalent in Asian populations and show an increased risk of intracranial haemorrhage [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although NOAC trial meta-analysis demonstrated greater proportional reduction compared with warfarin for rates of intracranial haemorrhage for Asian patients versus non-Asians, the absolute rates still remain higher [4,11]. Attention has also been focused on the possible link between macro and micro-angiopathies which are more prevalent in Asian populations and show an increased risk of intracranial haemorrhage [11]. Results from a Korean study suggested that among NVAF patients with a recent ischaemic stroke, 17.2% were classified as AF-unrelated, highlighting the complexity surrounding mixed aetiologies of stroke in Asians [12].…”
Section: Discussionmentioning
confidence: 99%